Intravitreal Bevacizumab in Management of Persistent Secondary Macular Hole with Epiretinal Proliferation - Zangmo, Ugyen; Jayanna, Sushma; Shanmugam, Mahesh P (Nepalese Journal of Ophthalmology, 2023)
Background: Aetiology for non-closure of full-thickness macular hole (FTMH) becomes crucial in determining the method of effective mode of intervention. Association of epiretinal proliferation (ERP) along with full-thickness macular hole (FTMH) have shown poorer anatomic and visual outcomes after surgical intervention. Various surgical techniques have been described in literature for treatment of persistent MH. Case: We report a A 60-year-old female patient with FTMH secondary to branched retinal vein occlusion (BRVO) initially associated with ERP. Observations: She was successfully managed by treating with combination of intravitreal injection of off label bevacizumab (Avastin) (1.25 mg/0.05 ml) and pure gas of SF6 (1 cc) under topical anaesthesia after an initial surgical intervention. Conclusion: Presence of ERP in retinal vein occlusion cases needs closer and frequent follow up. IVB can be used as an adjunct in treating secondary MH.